NO enhances the adaptability to high-salt environments by regulating osmotic balance, antioxidant defense, and ion homeostasis in eelgrass based on transcriptome and metabolome analysis - Wang, Xianyan; Wang, Tongtong; Yu, Pei; Li, Yuchun; Lv, Xinfang (Frontiers in Plant Science, 2024)
Eelgrass is a typical marine angiosperm that exhibits strong adaptability to high-salt environment. Previous studies have shown that various growth and physiological indicators were significantly affected after the nitrate reductase (NR) pathway for nitric oxide (NO) synthesis in eelgrass was blocked. To analyze the molecular mechanism of NO on the adaptability to high salt environment in eelgrass, we treated eelgrass with artificial seawater (control group) and artificial seawater with 1mM/L Na2WO4 (experimental group). Based on transcriptomics and metabolomics, the molecular mechanism of NO affecting the salt tolerance of eelgrass was explored. We obtained 326, 368 and 859 differentially expressed genes (DEGs) by transcriptome sequencing in eelgrass roots, stems, and leaves, respectively. Meanwhile, 63, 52 and 36 differentially accumulated metabolites (DAMs) were obtained by metabolomics in roots, stems, and leaves, respectively. Finally, through the combined analysis of transcriptome and metabolome, we found that the NO regulatory mechanism of roots and leaves of eelgrass is similar to that of terrestrial plants, while the regulatory mechanism of stems has similar and unique features. NO in eelgrass roots regulates osmotic balance and antioxidant defense by affecting genes in transmembrane transport and jasmonic acid-related pathways to improve the adaptability of eelgrass to high-salt environment. NO in eelgrass leaves regulates the downstream antioxidant defense system by affecting the signal transduction of plant hormones. NO in the stems of eelgrass regulates ion homeostasis by affecting genes related to ion homeostasis to enhance the adaptability of eelgrass to high salt environment. Differently, after the NO synthesis was inhibited, the glyoxylate and dicarboxylate metabolism, as well as TCA cycle, were regulated by glucose metabolism as a complementary effect to cope with the high salt environment in the stems of eelgrass. These are studies on the regulatory mechanism of NO in eelgrass, providing a theoretical basis for the study of the salt tolerance mechanism of marine plants and the improvement of terrestrial crop traits.The key genes discovered in this study can be applied to increase salt tolerance in terrestrial crops through cloning and molecular breeding methods in future.